Seasonal variation in the Carbohydrate content from different tissues of Sepia aculeata in Pazhayar coastal waters, Nagapattinam District, Tamilnadu - Sumathi, S.; Ponni, A. Christy (International Journal of Scientific Research in Biological Sciences, 2018)
The aim of this work was to investigate the seasonal variability in the Carbohydrate content in Sepia aculeata during January 2017 to December 2017. The total carbohydrate was estimated in muscle, gill, liver and gonad.